2021
DOI: 10.1177/1525822x21989841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Incentive Amount on U.S. Adolescents’ Participation in an Accelerometer Data Collection Component of a National Survey

Abstract: Behavioral research increasingly uses accelerometers to provide objective estimates of physical activity. This study extends research on methods for collecting accelerometer data among youth by examining whether the amount of a monetary incentive affects enrollment and compliance in a mail-based accelerometer study of adolescents. We invited a subset of adolescents in a national web-based study to wear an accelerometer for seven days and return it by mail; participants received either $20 or $40 for participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It is acknowledged that there are inherent challenges with using accelerometers to measure physical activity, particularly among adolescents such as compliance with wear time criteria, 55 and non‐return of devices 56,57 . However, having addressed the feedback from the YAG on incentives for compliance with accelerometer wear‐time criteria, we observed that an exceptionally low number of accelerometers were unreturned ( n 3; 0.14%) and across four time points, >84% of pupils met wear‐time criteria 55,57,58 . In the present study, the cost per YAG member attending the meeting was on average £54.63, but it is important to note that we did not capture researcher time, which would considerably increase the overall cost of this PPI work and would be an important consideration for future studies.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…It is acknowledged that there are inherent challenges with using accelerometers to measure physical activity, particularly among adolescents such as compliance with wear time criteria, 55 and non‐return of devices 56,57 . However, having addressed the feedback from the YAG on incentives for compliance with accelerometer wear‐time criteria, we observed that an exceptionally low number of accelerometers were unreturned ( n 3; 0.14%) and across four time points, >84% of pupils met wear‐time criteria 55,57,58 . In the present study, the cost per YAG member attending the meeting was on average £54.63, but it is important to note that we did not capture researcher time, which would considerably increase the overall cost of this PPI work and would be an important consideration for future studies.…”
Section: Discussionmentioning
confidence: 57%
“…56,57 However, having addressed the feedback from the YAG on incentives for compliance with accelerometer wear-time criteria, we observed that an exceptionally low number of accelerometers were unreturned (n3; 0.14%) and across four time points, >84% of pupils met wear-time criteria. 55,57,58 In the present study, the cost per YAG member attending the meeting was on average £54.63, but it is important to note that we did not capture researcher time, which would considerably increase the overall cost of this PPI work and would be an important consideration for future studies. For the YAG meetings outlined, members incurred no expenses; transport, meals and goody bags were provided.…”
Section: Discussionmentioning
confidence: 94%